Perceptions about teaching work in the initial training of rural educators: fabrics from the supervised curricular internship - Juliane Gomes de Sousa; Sônia Regina dos Santos Teixeira (Universidade Federal do Norte do Tocantins, 2023)
The article discusses the perceptions linked to teaching work, developed by students during the supervised curricular internship experiences (stage II), in the Degree in Rural Education: qualification in Arts (Visual Arts, Performing Arts and Music), offered at the Federal University of Northern Tocantins (UFNT). The investigative path was initially developed through a bibliographic review with the aim of conceptual deepening, followed by a referential inventory from the survey of theses and dissertations on the portal of the Brazilian Digital Library of Theses and Dissertations (BDTD), seeking to identify research carried out from 2014 to 2021, which place the supervised curricular internship in the initial training of teachers and the supervised curricular internship in the formative singularity of the degree in Rural Education. In addition to these resorted to, a documentary analysis was carried out on the internship reports prepared by the students, during Supervised Curricular Internship II, in the second half of 2018, the last offer of this stage in the modality in person in the period leading up to the COVID-19 pandemic, caused by the SARS-CoV-2 virus. From the analyzes carried out, two subcategories linked to teaching work were identified: Teacher professional training and Educator's role, considered interdependent according to the objective outlined for the investigation. It is concluded that the internship experiences help the student in training to develop understandings about becoming a professional. Perceptions about professional work, based on active and direct contact with the school environment, demonstrate that assuming the position of educator enables the identification of the functions assigned to it: difficulties, pleasures, experiences, development of pedagogical activities, planning, recognition of the diversity of people and realities, allowing the student - trainee to project the social roles that can be played in the exercise of the profession.